2004
DOI: 10.1038/sj.cgt.7700785
|View full text |Cite
|
Sign up to set email alerts
|

Use and specificity of breast cancer antigen/milk protein BA46 for generating anti-self-cytotoxic T lymphocytes by recombinant adeno-associated virus-based gene loading of dendritic cells

Abstract: Antigen-targeted immunotherapy is an emerging treatment for breast cancer. However, useful breast cancer antigens are only found in a subset of cancer patients. BA46, also known as lactadherin, is a membrane-associated glycoprotein that is expressed in most breast cancer cells but not in general hematopoietic cell populations. Moreover, it is much more difficult to generate CTLs against self-antigens. We wished to determine if the use of recombinant adeno-associated virus (rAAV) type 2 vectors for gene-loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…While the L form containing a Pro/Thr-enriched domain facilitates phagocytosis of apoptotic cells by macrophages (Hanayama et al, 2002(Hanayama et al, , 2004, the S form was reported to support the gamete interaction upon fertilization (Ensslin and Shur, 2003). Very importantly, recent studies determined peptide sequences derived from human MFG-E8 as the potential targets for tumor immunotherapy (Carmon et al, 2002;Liu et al, 2005).…”
mentioning
confidence: 99%
“…While the L form containing a Pro/Thr-enriched domain facilitates phagocytosis of apoptotic cells by macrophages (Hanayama et al, 2002(Hanayama et al, , 2004, the S form was reported to support the gamete interaction upon fertilization (Ensslin and Shur, 2003). Very importantly, recent studies determined peptide sequences derived from human MFG-E8 as the potential targets for tumor immunotherapy (Carmon et al, 2002;Liu et al, 2005).…”
mentioning
confidence: 99%
“…AAV1 [Veron et al, 2007], AAV2 [Liu et al, 2005;Ponnazhagan et al, 2001;Veron et al, 2007] and AAV6 [Aldrich et al, 2006] have been shown to transduce DC cultures ex vivo in studies aimed at achieving adaptive immunity to the vector encoded product (Fig. 1ab).…”
Section: Transgene Product Specific Immune Responsesmentioning
confidence: 96%
“…Since the immunotherapy has offered great promises for treatment of cancers, many approaches have been exploited to use AAV vectors to deliver genes to stimulate the immune response against tumors (39)(40)(41)(42)(43)(44)(45)(46)(47). Mohr et al demonstrated that the tumor growth in the mice transduced with an AAV2/TRAIL (tumor necrosis factor-related apoptosis-inducing ligand) vector was greatly suppressed (41).…”
Section: Immunotherapymentioning
confidence: 99%